2014
DOI: 10.1093/nar/gku609
|View full text |Cite
|
Sign up to set email alerts
|

dREAM co-operates with insulator-binding proteins and regulates expression at divergently paired genes

Abstract: dREAM complexes represent the predominant form of E2F/RBF repressor complexes in Drosophila. dREAM associates with thousands of sites in the fly genome but its mechanism of action is unknown. To understand the genomic context in which dREAM acts we examined the distribution and localization of Drosophila E2F and dREAM proteins. Here we report a striking and unexpected overlap between dE2F2/dREAM sites and binding sites for the insulator-binding proteins CP190 and Beaf-32. Genetic assays show that these compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 85 publications
0
23
0
Order By: Relevance
“…Other factors associated with cohesinindependent interactions include chromatin regulatory proteins such as NuRD-related factor PWWP2A, DREAM complex subunit LIN-9 and histone demethylase PHF8, which are known to be involved in the transcriptional control of the cell cycle (Liu et al, 2010;Pünzeler et al, 2017;Sadasivam and DeCaprio, 2013). Both PWWP2A and LIN-9 associate with H2A.Z histone variant (Latorre et al, 2015;Pünzeler et al, 2017), while interestingly, the DREAM complex was found to possess insulator activity in Drosophila (Bohla et al, 2014;Korenjak et al, 2014). Finally, an enrichment for H3K27me3 histone mark associated with Polycomb Repressive Complexes is consistent with the independent findings of a very recent study in ES cells (Rhodes et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Other factors associated with cohesinindependent interactions include chromatin regulatory proteins such as NuRD-related factor PWWP2A, DREAM complex subunit LIN-9 and histone demethylase PHF8, which are known to be involved in the transcriptional control of the cell cycle (Liu et al, 2010;Pünzeler et al, 2017;Sadasivam and DeCaprio, 2013). Both PWWP2A and LIN-9 associate with H2A.Z histone variant (Latorre et al, 2015;Pünzeler et al, 2017), while interestingly, the DREAM complex was found to possess insulator activity in Drosophila (Bohla et al, 2014;Korenjak et al, 2014). Finally, an enrichment for H3K27me3 histone mark associated with Polycomb Repressive Complexes is consistent with the independent findings of a very recent study in ES cells (Rhodes et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To better explore the relationship between Myb and insulator proteins, we focused on divergently paired genes (DPGs) because insulator proteins as well as some dREAM complex members have been shown to be present at these sites (Korenjak et al, 2014;Nè gre et al, 2010;Yang et al, 2012). We found that Myb bound to 84% of all Drosophila DPGs (p = 2.32 3 10 À275 compared to shuffled control), similar to the percentage of DPGs bound by CP190 and BEAF-32 (each approximately 86%), but much higher than the binding observed for other insulator-associated factors (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that several components of dREAM can bind insulator sites (Bohla et al, 2014;Korenjak et al, 2014), and RNAi depletion of Mip40, Mip130, and E2f2 resulted in impairment of enhancer-blocking function at specific sites (Bohla et al, 2014). Furthermore, components of dREAM (Myb, Mip120, Mip130, Rbf1, E2f2, and DP) were shown to directly interact with dCTCF and/or CP190 (Bohla et al, 2014;Korenjak et al, 2014). Interestingly, double knockdown of dCTCF and CP190 resulted in loss of dREAM (Mip40, Mip120, Mip130, and E2f2) at some shared sites (Bohla et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the phenotype of lint1 loss of function is weaker than the l(3)mbt phenotype suggesting that other protein complexes contribute to L(3)mbt boundary function. L(3)mbt also associates with the dREAM complex, some components of which have been shown to cooperate with insulator proteins to maintain transcriptional integrity at a subset of divergently-paired genes in Kc167 cells (Bohla et al 2014;Korenjak et al 2014). Further, E2f2 binding sites that possess enhancer-blocking properties are all co-occupied by L(3)mbt in Kc cells ).…”
Section: Discussionmentioning
confidence: 99%